Predictive analysis of catecholamines and electrolytes for recurrence of orthostatic intolerance in children - Chang, Lujie; Peng, Lu; Liu, Jianglin; Wang, Minmin; Li, Meng; Kong, Qingyu; Zhao, Haizhao; Zhao, Cuifen (Frontiers in Pediatrics, 2023)
Background Orthostatic intolerance (OI) is usually mediated by the autonomic nerve and most often happens in the upright position. However, it can also occur in other positions and can be relieved by lying down while likely to have another attack after relief. In the current study, we aim to evaluate the predictive effect of catecholamines and electrolytes on the recurrence of OI in children. Materials and methods Children who were diagnosed with vasovagal syncope (VVS), postural tachycardia syndrome (POTS), and VVS combined with POTS were enrolled in this retrospective study and were followed up after 1-year physical treatment. Catecholamines in urine collected within 24 h, renin, angiotensin II, aldosterone in plasma, and electrolytes in both blood and urine collected in the morning were tested. A multivariate analysis and a receiver operating characteristic curve were used to validate the prediction effect. Results In the VVS cohort, the 24 h urine adrenaline (AD) and norepinephrine (NE) levels of the non-recurrence group were lower than the 24 h urine AD and NE levels of the recurrence group, with a significant difference of P < 0.05. A different content can also be witnessed in the POTS cohort that the urine of the non-recurrence group contained lower sodium and chlorine. As for the VVS + POTS cohort, the non-recurrence group has lower AD and NE levels and higher potassium and phosphorus levels in urine, the difference of which proved prominent as well. Conclusion The study provides further evidence that AD, NE, and electrolytes in urine are promising factors that are closely related to the recurrence of OI in children. The integrated evaluation system merging AD and NE may have better predictive ability.